PENDAMPINGAN PENULISAN SURAT DINAS MENGGUNAKAN BAHASA INDONESIA YANG BAIK DAN BENAR BERBASIS ARTIFICIAL INTELLIGENCE, KBBI DARING, DAN EYD EDISI V BAGI PENGURUS BUMDES GIRI LODJI BALERANTE, KECAMATAN KEMALANG, KLATEN - Hendrawanto, Yusuf; Nastiti, Ana Putri; Devilito, Rio (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
BUMDes Giri Lodji Balerante is a business entity owned by Balerante Village which is a tourist village. The problem experienced by BUMDes members is the limited ability to write official letters. The Polines community service team carried out community empowerment activities in Balerante Village by providing assistance in writing official letters with the help of artificial intelligence, KBBI Online, and EYD edition V, attended by the management of BUMDes Giri Lodji Balerante. The community empowerment method was carried out through stages of socialization and implementation of assistance activities in writing official letters with the help of artificial intelligence, KBBI Online, and EYD edition V. The community service team also provided a guidebook for writing official letters with the help of artificial intelligence, KBBI Online, and EYD edition V to BUMDes. With the community service activities, the writing skills of BUMDes members' official letters increased.